ITF guide to recommended healthcare standards for tennis tournaments - Dunn, N.; Hainline, B.; Miller, S.; Montalvan, B.; Pluim, B.; Quinn, A.; Renström, P.; Stroia, K.; Weber, K.; Wood, T. (Medicine and Science in Tennis, 2009)
This paper aims to provide recommendations for the minimum standard of healthcare required at tennis tournaments. The recommendations in this document are split into two categories of tournament: 1) Tournaments organized by National Associations; 2) ITF Men's and Women's Pro Circuits and ITF Junior Circuit tournaments.